SOSIALISASI CARA PENANGANAN PASIEN GAWAT DARURAT DI PUSKESMAS BUNGURSARI - Wirdan Fauzi Rahman,; Serly, Serly (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Emergency events usually occur very quickly and suddenly so it is difficult to predict when and where they will occur. Emergency events, for example, are accidents that can happen anytime and anywhere. According to data from the Transportation Service Office of the Province of Surabaya, Purwakarta city occupies the first position as the city with the most traffic accidents, with the number of accident victims reaching 653, 77 fatalities, 115 seriously injured victims, 758 minor injuries. first aid in traffic accidents which cannot be done haphazardly, so it is necessary to see how bad the condition of the victim is and what help must be given immediately, especially for ordinary people as first aiders. The aim of the activity is to increase public knowledge and understanding of first aid for victims of traffic accidents. The method is carried out by providing socialization and education using booklet media about first aid for traffic accident victims. The activity was carried out involving 28 participants who are patients who often seek routine treatment at the Bungursari Health Center in Purwakarta. The results of this socialization and education activity can increase the community's knowledge of emergency first aid. The existence of this education is expected not only to provide knowledge but also to increase the confidence of the community to provide appropriate assistance according to the victim's condition and in accordance with victim assistance procedures